Congenital hypothyroidism and thyroid cancer. Issue 9 (22nd July 2021) - Penna, Gustavo; Rubio, Ileana G S; Brust, Ester Saraiva; Cazarin, Juliana; Hecht, Fabio; Alkmim, Nina Ramalho; Rajão, Kamilla M A Brandão; Ramos, Helton Estrela
Abstract : Differentiated thyroid carcinoma (DTC) combined with congenital hypothyroidism (CH) is a rare situation, and there is no well-established causal relationship. CH is a common congenital endocrine, while DTC occurring in childhood represents 0.4–3% of all malignancies at this stage of life. The association of CH with DTC could be related to dyshormonogenetic goiter (DHG) or developmental abnormalities. This review will explore the clinical features and the molecular mechanisms potentially associated with the appearance of DTC in CH: sporadic somatic driver mutations, chronic increase of thyroid-stimulating hormone (TSH) levels, higher concentrations of hydrogen peroxide (H2 O2 ), cell division cycle associated 8 (Borelain/ CDC8 ) gene mutations, and in others genes associated with CH – either alone or associated with the mechanisms involved in dyshormonogenesis. There are some pitfalls in the diagnosis of thyroid cancer in patients with CH with nodular goiter, as the proper cytological diagnosis of nodules of patients with dyshormonogenesis might be demanding due to the specific architectural and cytological appearance, which may lead to an erroneous interpretation of malignancy. The purpose of this article is to suggest an analytical framework that embraces the fundamental relationships between the various aspects of CH and CDT. In face of this scenario, the entire genetic and epigenetic context, the complex functioning, and cross talk of cell signaling may determine cellular mechanisms promoting both the maintenance of the differentiated state of the thyroid follicular cell and the disruption of its homeostasis leading to cancer. Whereas, the exact mechanisms for thyroid cancer development in CH remain to be elucidated.